Implementasi Trainer PLC Guna Pembelajaran Mekatronika Di Akademi Angkatan Udara - Bambang Gastomo; Edi Supartono; Muhammad Fahrurozi (Akademi Angkatan Udara, 2021)
The implementation of mechatronics learning packaged in the form of a PLC trainer goes through several stages including: needs analysis, model design, implementation, product testing and revision. Overall, the feasibility of PLC trainers based on the results of the feasibility test, namely the validation of media experts was declared very feasible with a percentage of 86.67%, material expert validation was declared very feasible with a percentage of 88.33%, while in the pretest and posttest with an average pretest value of 67 ,19 and post test 72,72. The results of the t-test stated that the value of tcount > ttable (8.288 > 2.042) and significance (0.000 <0.05), meaning that there was a significant difference in the average score of pretest and posttest cadets learning achievement scores with an increase in the learning percentage of 82.30%. It can be concluded that the implementation of the PLC trainer for teaching mechatronics is included in the very good category and is worthy of being used as a learning medium in order to improve AAU's student outcomes.